Physicochemical and Functional Properties and In Vitro Digestibility of Green Banana Flour-Based Snacks Enriched With Mango and Passion Fruit Pulps by Extrusion Cooking - Sarmiento-Torres, Luisa Fernanda; Murrillo-Franco, Sarha Lucia [UNESP]; Galvis-Nieto, Juan David; Rodríguez, L. Joana; Igual, Marta; García-Segovia, Purificación; Orrego, Carlos E. (Wiley, 2025)
Surplus banana crops that are not marketable, but still of suitable quality for consumption, are indeed a challenge in terms of underutilization as a post-harvest by-product. However, this situation also presents an exciting opportunity: these by-products can serve as a valuable raw material for the production of extruded snacks. This study examines the impact of incorporating passion fruit and mango pulp (6% w/w) into green banana flour on physicochemical properties, pre- and postextrusion cooking, and bioactive compound content, alongside their bioaccessibility during in vitro digestion. Proximate composition analysis revealed that there were no significant changes in lipid and protein content following extrusion. However, there was a notable decrease in fiber due to alterations in starch. Initial values for zinc, sodium, and calcium in banana flour were 0.678 mg/100 g, 9.237 mg/100 g, and 14.214 mg/100 g, respectively. Extrusion resulted in an increase in zinc content (1.032, 0.736, and 0.999 mg/100 g), sodium content (21.904, 17.608, and 18.787 mg/100 g), and calcium content (28.217, 16.884, and 58.207 mg/100 g) in the banana flour extrudates without pulp, with passion fruit pulp, and with mango pulp, respectively. The addition of fruit pulp significantly enhanced the total phenolic compounds and carotenoids, though thermal degradation reduced the compound content postextrusion. Texture analysis demonstrated no significant differences among the samples, which were found to have hardness and crispness values consistent with those reported in the literature, at 20–25 N for hardness and 100–117 for crispness. In vitro digestion demonstrated increased bioaccessibility of total phenolic compounds, flavonoids, and carotenoids in extrudate samples compared to raw mixtures. The enhancements were 41%–72% for total phenolics, 100% for flavonoids, and 22%–78% for carotenoids. The utilization of surplus green banana represents a valuable alternative to produce healthy and functional snacks enriched with fruit pulps.